2021
DOI: 10.1021/acsanm.1c00139
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Nanoparticle Filtration by Filtering Facepiece Respirators During the COVID-19 Pandemic

Abstract: The onset of the COVID-19 pandemic in spring 2020 resulted in a spike in the demand for face masks and respirators. Due to their effectiveness at filtering aerosols that could potentially contain viruses, the N95-type filtering facepiece respirators (FFRs) are frequently used by healthcare workers and first responders. However, due to a shortage of domestic N95 FFRs in the US at the beginning of the pandemic, internationally produced respirators were imported and deployed under an Emergency Use Authorization b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…45 Respirators such as N95s are made of several nonwoven synthetic layers and offer better virus filtration due to electrostatic charges and a close seal to the face. 46 The ultrafine filtration layer is typically composed of meltblown polypropylene, that is then placed between multiple other polyester layers. Respirators are likely to be better than surgical masks for sun protection due to their polyester content.…”
Section: Medical Masksmentioning
confidence: 99%
“…45 Respirators such as N95s are made of several nonwoven synthetic layers and offer better virus filtration due to electrostatic charges and a close seal to the face. 46 The ultrafine filtration layer is typically composed of meltblown polypropylene, that is then placed between multiple other polyester layers. Respirators are likely to be better than surgical masks for sun protection due to their polyester content.…”
Section: Medical Masksmentioning
confidence: 99%
“…In a recent study, Hao et al [31] examined the effectiveness of 136 filtering facepiece respirators of the N95-type and revealed that a significant percentage of the respirators fell notably below their claimed performance level. The fit factor differences of the different respirators used in this study were not analyzed due the sample size not being adequate to compare these three conditions, but these differences could have influenced our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Donning face masks and social distancing have been the primary tools in mitigating droplet and airborne transmission [1,2]. It is well-known that proper material designs can be employed to reach a high filtration efficiency and proper pressure drop through mask fabrics [3][4][5]. However, when the mask is fabricated from the cloth or is loosely placed on the face, its efficacy decreases significantly due to leakage around the perimeter of the mask [6,7].…”
Section: Introductionmentioning
confidence: 99%